Spirituality and meaning of life in nursing education: report of experience in teaching - Angelica Yolanda Bueno Bejarano Vale de Medeiros; Eliane Ramos Pereira; Rose Mary Costa Rosa Andrade Silva; Renata Carla Nencetti Pereira Rocha; Elisabete Correa Vallois; Diva Cristina Morett Romano Leão
ABSTRACT Objectives: To report the experience in teaching internship in the elective discipline "Spirituality in the Health Field" of the curriculum of the graduation course in Nursing of Universidade Federal Fluminense. Methods: This is a case report with descriptive-reflexive approach of the class "the meaning of life as spiritual care strategy in the nursing practice". For the elaboration of the discipline, a lesson plan and active methodologies were used. Results: The strategy used for preparation of the class allowed transmitting and constructing knowledge objectively. The reflections disclosed along with students showed the importance of the meaning of life as spiritual care in nursing practices for the health professional and for the act of being cared for. Final considerations: The class was considered a successful experience, as the theme proposed was essential for the theoretical-reflective construction about spirituality and meaning of life as a form of care that transcends technical procedures.